La ejecución presupuestal y el cumplimiento de las metas en la Municipalidad Distrital de San Juan Bautista en el periodo 2018 – 2022 - Ruiz Ferreira, Almendra Gianella (2024)
Between the years 2018 - 2022, a Pearson correlation analysis was carried out to evaluate the relationship between the execution of income, the execution of expenses, and the achievement of goals in the District Municipality of San Juan Bautista. The results showed moderate positive correlations between these variables, with a coefficient of 0.7644 between the execution of income and the execution of expenses, 0.4922 between the execution of expenses and the goals achieved, and 0.6292 between the execution of income and the goals. However, none of these correlations were statistically significant, as p values were greater than 0.05, indicating that the observed relationships could be a product of chance and not representative of the population. The lack of statistical significance may be due to the small sample size, which limits the ability to make conclusive statements about financial management and goal achievement in the municipality. These findings suggest the need to improve data collection, optimize planning and resource allocation, and consider other qualitative factors that may be influencing municipal performance during this period.